Analyzing The Electoral Reform Journey of Indonesia From 2004-2023: Value Demands or Power Needs? - Suci, Perwita; Suri, Ihsan (Jurnal Politica, 2024)
Why does electoral reform rarely occur in Indonesia? Several experts believe thatpoliticians are the main actors behind electoral reform in the world. With a varietyof background motivations, electoral reform usually occurs because of the interestin achieving or perpetuating power. On the other hand, this article sees that not allelectoral reforms that occurred were initiated by politicians. Several electoral reformphenomena occurred based on pressure from the public, judges, and experts. Weargue that electoral reforms initiated by actors other than politicians are a responseto the failure of the electoral system. We illustrate this view using a case study ofelectoral reform in Indonesia in the period 2004-2023.